Alternate wetting and drying technology outscaled on 180,000ha of rice production in Vietnam, reducing over 1 million tCO2-eq/yr. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Vietnam's Ministry of Agriculture and Rural Development have used IRRI-CCAFS research findings and institutionalized IRRI-CCAFS's recommendations for alternate-wetting-and-drying (AWD) in the national implementation plan for Vietnam's NDC in agriculture as well as technical guidelines for nation-wide application. By 2019, at least ten development organizations and private companies have promoted AWD technology in eleven provinces to mitigate greenhouse gas (GHG) emissions in Vietnam, reaching 180,000 hectares and reducing GHG emissions by 1,118,820 tCO2e annually.